Fukuda Stepping Test sebagai Upaya Promotif dan Preventif Gangguan Keseimbangan Tubuh pada Lansia - Catherine Hermawan Salim; Astrid Komala Dewi; Ribka Sabarina Panjaitan; Wirya Limala Putra; Kayla Salina; Annisa Nadila Ramadani (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Balance disorders are among the most common functional problems experienced by older adults and significantly increase the risk of falls, disability, and reduced quality of life. Early screening and health promotion efforts are essential in preventing these complications. This community service program aimed to introduce and implement the Fukuda Stepping Test as a simple, low-cost, and effective method for promotive and preventive assessment of balance impairment among elderly individuals in the community. The activity involved health education on balance maintenance, demonstration of the test procedure, and direct assessment of participants, followed by individualized feedback and recommendations for balance exercises. The results showed that the Fukuda Stepping Test was well-received, easy to perform, and successfully identified elderly individuals with potential vestibular asymmetry or dynamic balance deficits. Furthermore, the program increased participants’ awareness regarding fall prevention and encouraged adoption of regular balance training. This initiative highlights the importance of accessible physiotherapy-based screening tools in community settings and underscores the role of physiotherapists in promoting healthy aging and reducing fall risk among older adults.